Employing electronic video journalism in news coverage: A field study on a sample of Saudi journalists (The International Journal of Educational Sciences and Arts, 2026)
The current study aimed to identify video journalism and its patterns by answering the main question of the study: What is the extent of the use of electronic video journalism in news coverage from the point of view of Saudi journalists? Where the study crystallizes around this question and seeks through it to monitor the most productive topics in electronic video journalism from the point of view of Saudi journalists. The researcher used the descriptive analytical method within the study, as it fits with the quality of the quantitative study, which seeks to analyze the phenomenon of video journalism within the Saudi society, with the use of the survey method in collecting data for analysis afterwards through the questionnaire that was distributed to the study sample, where a sample consisted of (73). An individual was selected from the study population, the Saudi journalists. The study reached a set of results, most notably: that the most used journalistic topics for video journalism are press reports with a percentage of 91%, then news in second place with 89.3%, and narrative and illustrated stories in third place, which got a percentage of 82.3%, and the most content that Covered by video journalism, social content came first and got a percentage of 97.3%, then it was followed in the list of sports content, and the results of the questionnaire confirmed that the scale of the use of social media in spreading video journalism came in support of the YouTube platform YouTube in the first place by 94%, and it came in the center The second is the famous Twitter platform, Twitter, with a rate of 91.3%. The study also recommended the need to pay attention to the field of news and awareness video industry within the colleges of media and mass communication in the Kingdom of Saudi Arabia and Arab societies in general, with the need to organize training courses for workers in the field of traditional journalism to spread the culture of using technology and video as a means of transmission News faster and better.
Keywords: Online Video Journalism; News Coverage; Saudi Journalism